Wild bee and floral diversity co‐vary in response to the direct and indirect impacts of land use. Issue 11 (22nd November 2017) - Papanikolaou, Alexandra D.; Kühn, Ingolf; Frenzel, Mark; Kuhlmann, Michael; Poschlod, Peter; Potts, Simon G.; Roberts, Stuart P. M.; Schweiger, Oliver
Abstract: Loss of habitat area and diversity poses a threat to communities of wild pollinators and flowering plants in agricultural landscapes. Pollinators, such as wild bees, and insect‐pollinated plants are two groups of organisms that closely interact. Nevertheless, it is still not clear how species richness and functional diversity, in terms of pollination‐relevant traits, of these two groups influence each other and how they respond to land use change. In the present study, we used data from 24 agricultural landscapes in seven European countries to investigate the effect of landscape composition and habitat richness on species richness and functional diversity of wild bees and insect‐pollinated plants. We characterized the relationships between the diversity of bees and flowering plants and identified indirect effects of landscape on bees and plants mediated by these relationships. We found that increasing cover of arable land negatively affected flowering plant species richness, while increasing habitat richness positively affected the species richness and functional diversity of bees. In contrast, the functional diversity of insect‐pollinated plants (when corrected for species richness) was unaffected by landscape composition, and habitat richness showed little relation to bee functional diversity. We additionally found that bee species richness positively affected plant species richness and that bee functional diversity was positively affected by both species richness and functional diversity of plants. The relationships between flowering plant and bee diversity were modulated by indirect effects of landscape characteristics on the biotic communities. In conclusion, our findings demonstrate that landscape properties affect plant and bee communities in both direct and indirect ways. The interconnection between the diversities of wild bees and insect‐pollinated plants increases the risk for parallel declines, extinctions, and functional depletion. Our study highlights the necessity of considering the interplay between interacting species groups when assessing the response of entire communities to land use changes.